STUDIES ON THE PROTEIN RESERVE I EFFECTS OF SUBCUTANEOUS INJECTION OF OCULAR LIQUIDS ON THE GROWTH OF THE WHITE RAT - TAPIA, MARCO A; SOTO VERGARA, EDUARDO; CABRERA, GUILLERMO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
A case of bilateral partial absence of the radius with the associated deformity of the hands was descr in an 11-yr-old Tarascan Indian girl from Michoacan, Mexico With few exceptions, the 292 previously reported cases of congenital absence of the radiu
CIENC MEX
Keywords: STUDIES, PROTEIN RESERVE, EFFECTS, SUBCUTANEOUS INJECTION, OCULAR LIQUIDS, GROWTH, WHITE RAT; MULTIDISCIPLINARIA; BIOLOGIA ANIMAL; RATAS